Teenagers, Digital Media, and Language Development: An Exploration of Potential and Challenges in Promoting English Skills - Nofianto, Norma; Puspitasari, Dewi; Maulida, Chusna (Journal of English Teaching and Learning Issues, 2020)
Digital media has a significant role in the development of English for teenagers. The rapid development in digital technologies enables the teacher to be creative and innovative in teaching a second language, it can be used as a tool to enhance language learning, through increasing the opportunities for contact with native speakers and input from the target language. The research design used in this study was a literature study and collected data through navigating some relevant studies relating to social media. The researchers chose and analyzed the information about the potential and challenges of digital media in promoting English language development for teenagers. The challenges of fostering English language development through digital media in teenagers based on literature reviews are teachers’ problems. Digital media is a potential aid of promoting English language development in teenagers depends on the ability of teachers to minimize the challenges.